2018
DOI: 10.1111/all.13421
|View full text |Cite
|
Sign up to set email alerts
|

IgE‐expressing memory B cells and plasmablasts are increased in blood of children with asthma, food allergy, and atopic dermatitis

Abstract: Despite the critical role of soluble IgE in the pathology of IgE-mediated allergic disease, little is known about abnormalities in the memory B cells and plasma cells that produce IgE in allergic patients. We here applied a flow cytometric approach to cross-sectionally study blood IgE+ memory B cells and plasmablasts in 149 children with atopic dermatitis, food allergy, and/or asthma and correlated these to helper T(h)2 cells and eosinophils. Children with allergic disease had increased numbers of IgE+CD27- an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(93 citation statements)
references
References 27 publications
3
85
2
2
Order By: Relevance
“…B cells play a crucial role in the sensitization and adaptive immune response of asthma (Table ) . Admyre et al concluded that B cell–derived exosomes play a role in stimulating the allergic immune response.…”
Section: Resultsmentioning
confidence: 99%
“…B cells play a crucial role in the sensitization and adaptive immune response of asthma (Table ) . Admyre et al concluded that B cell–derived exosomes play a role in stimulating the allergic immune response.…”
Section: Resultsmentioning
confidence: 99%
“…Exponential advances in microarrays, time-of-flight mass cytometry (CyTOF), basophil activation tests, next-generation gene sequencing, and RNA-seq are generating huge enabling datasets. 15,115,116,[119][120][121][122][123] The risk that small populations of highly pathogenic cells might be masked by abundant signatures of more frequent or more active cells is combated by the emergence of enhanced single B-and T-cell immunophenotyping using flow cytometry-based assays. This allows longitudinal immunoprofiling of relevant cell subsets in individuals before and during AIT.…”
Section: Precision Medicine and Immune Monitoring Of Allergic Diseasesmentioning
confidence: 99%
“…The CD4 + CD25+CD127‐ phenotype specifically distinguishes human Treg, and these cells can be quantified in allergic patients with increases following SLIT for grass pollen and AIT in HDM‐allergic individuals . Furthermore, chemokine receptor expression patterns correlate strongly with Th cell function and can be used to identify Th1 (CCR6‐CXCR3 + CCR4‐), Th2 (CCR6‐CXCR3‐CCR4+) and Th17 (CCR6 + CXCR3‐CCR4+) subsets within CD4 memory cell populations (CD4 + CD45RA‐) . Grass pollen immunotherapy was shown to reduce the percentage of CCR3 + CD4+ cells in fresh PBMC of allergic rhinitis patients to levels similar to those in normal individuals .…”
Section: Candidate Biomarkers For Immune Monitoring In Allergen Immunmentioning
confidence: 99%
“…With the advances in multi‐parameter flow cytometry and the availability of many fluorochromes with high staining intensity, it has become possible to detect IgE‐expressing B cells following exclusion of naïve B cells that have bound IgE through surface CD23 as well as memory B cells expressing other Ig isotypes . This approach is technically demanding, and high cell numbers and an optimized flow cytometry panel are required for reliable detection . Similar to total and specific IgE in serum, blood IgE‐expressing B cells are increased in adults with atopic dermatitis, and in children with asthma, food allergy and atopic dermatitis .…”
Section: Candidate Biomarkers For Immune Monitoring In Allergen Immunmentioning
confidence: 99%